1968
DOI: 10.1113/jphysiol.1968.sp008411
|View full text |Cite
|
Sign up to set email alerts
|

A relation between the chain length of fatty acids and the slowing of gastric emptying

Abstract: SUMMARY1. Test meals of solutions and suspensions of potassium and sodium salts of a series of saturated fatty acids, from C2 to C1l, were given to healthy subjects.2. From the volume of these meals recovered after a fixed interval the relative effectiveness of the salts of the acids in slowing gastric emptying was assessed.3. On a molar basis the salts of fatty acids from acetic up to decanoic were relatively ineffective in slowing gastric emptying.4. The salts of fatty acids with 12-18 carbon atoms were much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
115
0
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(122 citation statements)
references
References 13 publications
6
115
0
1
Order By: Relevance
“…It has been established that the presence of C12 in the small intestinal lumen slows gastric emptying (16,19), stimulates isolated pyloric PWs (12), increases proximal gastric relaxation (19), suppresses antral (12,23) and duodenal motility (12), and stimulates the release of CCK (12,23) and GLP-1 (12). The current study extends these observations by demonstrating that the responses are dependent on the dose of C12 administered to the small intestine and that even very low doses of C12 have potent effects.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…It has been established that the presence of C12 in the small intestinal lumen slows gastric emptying (16,19), stimulates isolated pyloric PWs (12), increases proximal gastric relaxation (19), suppresses antral (12,23) and duodenal motility (12), and stimulates the release of CCK (12,23) and GLP-1 (12). The current study extends these observations by demonstrating that the responses are dependent on the dose of C12 administered to the small intestine and that even very low doses of C12 have potent effects.…”
Section: Discussionsupporting
confidence: 71%
“…(16). The 0.4 kcal/min load, albeit at a lower concentration, was selected on the basis of our previous study (12) in which C12 was administered intraduodenally at 0.375 kcal/min (106 mmol) to healthy subjects and shown to potently suppress energy intake.…”
Section: Preparation and Doses Of C12 Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…[23][24][25] Especially, the delayed gastric emptying by food was reported to have the potential to increase absorption of poorly water-soluble drugs including DRN by increasing the time available for drug dissolution. 26,27) The high dissolution rate of DRN in weak acid in both formulations also might be contributed to diminish the formulation effect on intestinal absorption under post-prandial state. It was reported that DRN is well absorbed (≈70% to 94%) after oral administration of the marketed product, although the absolute BA of DRN is only 15% when given with food in healthy subjects.…”
Section: In Vivo Absorption Study In Beagle Dogsmentioning
confidence: 99%